2019
DOI: 10.35872/jurkeb.v11i01.326
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Sosial Budaya Dan Peran Petugas Kesehatan Dengan Perilaku Pemberian Mp-Asi Dini Pada Bayi Usia 0-6 Bulan

Abstract: Mohamad Sadli  Program Studi Kesehatan Masyarakat STikes CirebonE-mail: msadli333@gmail.com.ABSTRAKMasa pertumbuhan bayi adalah masa yang kritis sehingga pemberian makanan harus selalu diperhatikan baik proses, jenis dan jumlahnya. Makanan tambahan yang diberikan kepada bayi selain ASI setelah bayi berusia 6 bulan sampai bayi berusia 24 bulan akan memenuhi kebutuhan gizi bayi tetapi kenyataanya sebelum usia 6 bulan banyak bayi yang sudah diberi MP-ASI. Berdasarkan data yang diperoleh dari UPT Puskesmas Pulasar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Likewise, Afriyani's research in 2016 at BPM Nurtila Palembang in 2016 that there is a relationship between tradition or culture (p-value = 0.004 and OR = 16,000) with the provision of complementary feeding to infants aged 0-6 months (Afriyani., 2016). Sadli's research in the UPT Puskesmas Pulasaren Cirebon City shows that from the results of statistical tests it was found that socioculture (p = 0,000) had a significant relationship with the behavior of early complementary breastfeeding in infants aged 0-6 months (Sadli, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Afriyani's research in 2016 at BPM Nurtila Palembang in 2016 that there is a relationship between tradition or culture (p-value = 0.004 and OR = 16,000) with the provision of complementary feeding to infants aged 0-6 months (Afriyani., 2016). Sadli's research in the UPT Puskesmas Pulasaren Cirebon City shows that from the results of statistical tests it was found that socioculture (p = 0,000) had a significant relationship with the behavior of early complementary breastfeeding in infants aged 0-6 months (Sadli, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with research conducted by Mohamad, who found that sociocultural support (p < 0.001) had a significant relationship with the behavior of giving early MP-ASI to babies aged 0-6 months. The environment here refers to the family, the place of work, and the household environment such that it results in giving early MP-ASI [14]. On the other hand, mothers who are not easily influenced by various existing beliefs or traditions have positive sociocultural support.…”
Section: Discussionmentioning
confidence: 99%
“…The The health worker support questionnaire consists of 10 questions which are adapted from Jannah's (2015). The scoring system of health worker support is using Likert scale as a score of 1 = never, 2 = sometimes, 3 = often, and 4 = always, with the category of less support (7)(8)(9)(10)(11)(12)(13)(14), sufficient support (15-21), and good support (2-28).…”
Section: Methodsmentioning
confidence: 99%
“…Knowledge regarding the importance of exclusive breastfeeding not only for wives but also for husbands. This is due to the husband's function as the head of the family, where the knowledge had an influence or be taken into consideration when making decisions, such as the mother's decision to breastfeed, the mother's commitment to breastfeed, and the length of time the mother breastfeeds her baby [13], [14]. This can minimize mistakes in decision-making in exclusive breastfeeding.…”
Section: Knowledgementioning
confidence: 99%